Evaluation of apical debris extrusion and patency file in continuous and reciprocating rotary endodontic systems. - Tomas Bordagaray; Karin Steinfort; Martin Pendola; Hector Monardes; Jaime Abarca (Universidad de Concepción., 2019)
The aim of the study was to quantify and compare apical debris extrusion in two systems of continuous and reciprocating rotary instrumentation with, and without, the use of a patency file. An experimental study was carried out in 120 mesial roots of lower first molars, which were randomized in the following 4 groups: Group A. Reciproc (VDW) R25 without a patency file, Group B Mtwo (VDW) without a patency file, Group C Reciproc (VDW) R25 with a patency file and Group D Mtwo with a patency file. Groups A, B and C presented statistically significant differences in comparison to group D, Mtwo with the use of a patency file (p<0.008 to 95% reliability). In conclusion, the greater amount of debris extruded through the apex occurred in roots instrumented with the reciprocating rotary system; this difference was statistically significant in relation to teeth treated with the Mtwo continuous rotary system with the use of a patency file.